Students' Arguments in Solving Probability Theory Problems Based on The Toulmin Argumentation Model - M. Zainul Arifin; Hendro Permadi (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
The role of arguments in solving mathematical problems is very important. Students must use valid arguments and concepts that have been learned in the Probability Theory material to build their arguments. An argument can be analyzed using the Toulmin scheme. Therefore, the purpose of this study is to describe the arguments that have been built based on the Toulmin Argumentation Model. The instrument used to collect data is a test question related to the Probability Theory material. Of the 32 students who worked on the test questions, three students were selected as research subjects. The selection of research subjects is based on the ability of students' mathematical ability level in working on test questions. It was found that students can construct an argument starting with the correct data. However, they did not give any Warrant and did not even give a Claim to their argument. This makes the argument built by students is invalid